The Influence of Financial Risk Attitude and Financial Risk Tolerance on MSME Risk Management Strategies in West Pasaman - Mia Muchia Desda (Journal of International Accounting, Taxation and Information Systems, 2025)
This study aims to examine the influence of financial risk attitude and financial risk tolerance on risk management strategies in Micro, Small, and Medium Enterprises (MSMEs) in West Pasaman Regency. A quantitative approach was used in this research, employing Partial Least Square-based Structural Equation Modeling (SEM-PLS) analysis method. Data was obtained from 120 MSME operators through questionnaires developed from valid indicators. The research results show that both risk attitude and risk tolerance have positive and significant effects on the applied risk management strategies. This finding indicates that the psychological dimensions of business operators play an important role in managerial decision-making for risk mitigation. The practical implications of this research emphasize the need to improve financial behavioral capacity in MSME empowerment.